Significance of risk assessment metric in audit of financial statements and reports - Wágner, Vilmos (Acta Agraria Debreceniensis, 2009)
Management and decision-support of today’s businesses require design and application of management reports based and high-end controlling systems. One of the main source of information for controlling systems is financial accounting that should be designed to support planning, controlling and monitoring systems. Financial and accounting information is essential for decision making support of organizations. Thereforeeligible assurance is needed that these information are true and fair. Internal and external financial audits as assurance qualifiers are linking to the controlling systems through assurance. Weaknesses of and threats to controlling systems shall be recovered and communicated to the management during qualifying process. Recovering of threats should be based on risk analysis, assessment. In this study I would like to present some methods and tools of risk assessment of financial reports, statements and a way on they can be further developed.